Development in Prescriptions of Contraindicated and Potentially Harmful QT Interval-Prolonging Drugs in a Large Geriatric Inpatient Cohort From 2011 to 2021 - Then, Melanie; Tuemena, Thomas; Sledziewska, Anna; Gassmann, Karl-Guenter; Maas, Renke; Fromm, Martin (Clinical Pharmacology & Therapeutics, 2023)
Regulatory authorities put major emphasis on QT (interval)-prolonging properties of new molecular entities. Product information/Summaries of Product Characteristics (SmPCs) of multiple drugs contain warnings or contraindications regarding QT prolongation, e.g., on coadministration of QT-prolonging drugs (QT drugs). To characterize the development of the QT drug burden, we performed a trend analysis of prescriptions and co-prescriptions of QT drugs in a large geriatric inpatient cohort. The German SmPCs (status of 2014 and of 2021) and the year-wise listings in the CredibleMeds((R)) database from 2011 to 2021 were used as sources. There were 402,631 geriatric cases included. The group of QT drugs according to SmPCs in 2014, which must not be combined with other QT drugs, was less frequently involved in contraindicated co-prescriptions in 2021 compared with 2015 (3.0% (2.5-3.7%) of cases with at least one of those drugs in 2021 vs. 4.0% (3.5-4.5%) in 2015), with citalopram, escitalopram, and amiodarone involved in nearly 90% of the co-prescriptions. The number of CredibleMeds-QT-drugs per patient increased from 0.4 (SD=1.1) in 2011 to 1.8 (SD=3.9) in 2021. The percentage of contraindicated co-prescriptions of drugs with known risk for torsade de pointes according to CredibleMeds((R)) listings at the beginning of the respective years increased from 1.7% in 2011 to 6.1% in 2021. Considering the regularly updated CredibleMeds((R)) QT drugs list, the contraindicated co-prescriptions of QT drugs markedly increased in the last decade. If prescribers considered only the few most frequently (co-) prescribed QT drugs, then most of the medication errors regarding QT drugs could be prevented.
CRIS-Team WoS Importer:2023-01-27